(1) بحث خزن واسترجاع المعلومات( المسترال )-بحث توثيقي study of information storage and retrieval (MISTRAL) - Documentation research - الوليد الشافعي (معهد التخطيط القومي, 2026)
هذا الملف هو بحث توثيقي بعنوان "الميسترال (Mistral)"، صادر عن مركز الوثائق بمعهد التخطيط القومي عام 1970. يستعرض البحث نظاماً آلياً متطوراً لتخزين واسترجاع المعلومات باستخدام الحاسب الإلكتروني، ويوضح قدرته على معالجة ملايين الوثائق وتنظيمها في حقول متنوعة (كالعنوان والمؤلف والكلمات الدالة)، مع مرونة عالية في إدخال البيانات وتعديلها دون التقيد بخانات أو أطوال محددة، مما يجعله أداة فعالة لخدمة البحث العلمي والتوثيق في تلك الحقبة. كما يتناول الملف الجوانب التقنية لتشغيل النظام، بما في ذلك كيفية صياغة "الأسئلة" للبحث عن المعلومات باستخدام المعادلات المنطقية (Boolean Equations)، وطرق استجابة النظام وتصحيحه للأخطاء آلياً. ويفصل البحث المكونات المادية المطلوبة لتشغيل "الميسترال" على أجهزة الحاسب الآلي المتاحة آنذاك (مثل IRIS 50 و10 070)، مع شرح لمستويات السرية وتكوين قواميس الكلمات والمترادفات التي تضمن دقة وسرعة الوصول إلى المعلومات المطلوبة. This document is a research paper titled "Mistral," published by the Documentation Center of the National Planning Institute in 1970. It reviews a sophisticated automated system for storing and retrieving information using computers. The paper demonstrates the system's ability to process and organize millions of documents into various fields (such as title, author, and keywords), with high flexibility in data entry and modification without being restricted by specific columns or lengths. This made it an effective tool for scientific research and documentation during that era. The document also addresses the technical aspects of operating the system, including how to formulate "questions" for information retrieval using Boolean equations, and how the system automatically responded to and corrected errors. The paper details the hardware components required to run "Mistral" on the computers available at the time (such as the IRIS 50 and 10070), explaining the levels of security and the creation of dictionaries and synonyms that ensured accurate and rapid access to the required information.